Smart electric control using MC68HC11 [compact disc] - 407489 Wan Huzaifah Wan Hassan (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2003